Heaven sent [videorecording (DVD)] - Abercrombie, Karen, 1956-; Pridgen, J. Leon; Tilton, Charlene; Dourdan, Gary (Mill Creek Entertainment, 2023)
Pastor Patrick has been a widower for fifteen years. A chance meeting with a free-spirited woman from the other side of the tracks turns out to be a true gift from heaven.